Penerapan Metode CPM (Critical Path Method) dalam Manajemen Servis Ganset Caterpillar di PT. Sigma Quantum Insani Balikpapan Kalimantan Timur - Erwin Erwin; Purbawati Purbawati; Diyaa Aaisyah Salmaa Putri Atmaja; Ida Rosanti (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Generator Set Service Management is the process of organizing maintenance, repair, and upkeep activities of generator sets, starting from planning, implementation, evaluation, control, and improvement of services to ensure the generator machine continues to operate effectively and efficiently. The research was conducted at PT. Sigma Quantum Insani, located in Balikpapan, East Kalimantan. The problem addressed in the research is the frequent delays in completing scheduled tasks within the generator set service management activities. The purpose of the study is to determine the critical path of activities and identify the duration of the critical path. From the analysis using the Critical Path Method (CPM) assisted by MS Project software, the identified critical path activities are: A1-B1-B2-B3-B4-B5-B6-B7-B8-B9-B10-B14-B16-B17-C1-C2-D1-D2-D3, which include DO approval, engineering scope, painting scope, and delivery scope. The total time obtained for the critical path is 38 days, resulting in a time efficiency of 8 days in the generator set service process.